LinkedIn as the upcoming recruitment tool and top management, graduates and student’s exposure to LinkedIn in Bangladesh - Adit, Ahmad Ullah (BRAC University, 2016)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2015.